Recent enhancements in ScaleNet: a queriable systematic database of the scale insects of the world (Hemiptera: Coccoidea) (Bollettino di zoologia agraria e bachicoltura, 2024)
A number of changes have been implemented in ScaleNet since it was last discussed in 1998 at the International Symposium on Scale Insect Studies. These changes include addition of databases on the following 18 families: Aclerdidae, Beesoniidae, Carayonemidae, Cerococcidae, Dactylopiidae, Grimaldiellidae, Halimococcidae, Inkaidae, Jersicoccidae, Kermesidae, Kerriidae, Kukaspididae, Labiococcidae, Lecanodiaspididae, Micrococcidae, Phenacoleachiidae, Phoenicococcidae, and Stictococcidae making a total of 23 families on line. The bibliographic file has grown from 11,000 to over 14,700 references and a system has been developed to look for variant spellings of author names. A new query has been added that allows a search for a string of letters in a species epithet and very soon a section on on invasive species will be added. The "Scales in a Region/Country/Subunit Query" now allows a search for all of the species in a zoogeographic region, country, or country subunit in a particular scale family or genus. The "Hosts, Natural Enemies and Associates of a Scale Query" allows a search for all of the species that are found on a specified host, have specified natural enemies, or have specified associates in a particular scale family or genus. Significant progress has been achieved  on the armored scale, margarodid, and asterolecaniid databases.
Keywords: Coccoidea; ScaleNet; information; internet; web